STATUS OF THE SPLEEN AFTER LIGATURE THE SPLENIC ARTERY DURING EXPERIMENTAL PORTAL HYPERTENSION - Prokopets, К.О.; Raskaliei, T.I. (World of Medicine and Biology, 2018)
Aim. With the help of macro and microscopic methods, spleen changes after the operation of the ligation of the splenic artery - in the case of experimental portal hypertension - have been investigated in order to detect the possibility of applying an operation for the correction of portal hypertension. Materials and methods. The study was performed on 24 rats - male Vistar albicans at the age of 7 months. The experiment was guided by the provisions of GLP (1981), the ethical principles of the European Convention for the Protection of Vertebrate Animals. Animals of the main group performed the simulation of chronic hepatocellular hypertension. Correction of the existing portal hypertension was carried out by dressing the splenic artery on the 30th day after its modeling. Method of anesthesia – total anesthesia (intraperitoneally 10% solution of sodium thiopental, 0.5 ml per 100 g of weight). Animals were extracted from the experiment by increasing the concentration of anesthetic after performing laparotomy and measuring the pressure in the portal vein of the liver. Control was a material are taken from 5 animals that had not been operated.For histological examination, fragments of the spleen were taken up to 5 mm in thickness from different parts of it. Coloring - by hematoxylin and eosin and by the method of van Gieson. The morphometric indices of the spleen were determined:• the specific weight of the capsule and trabeculae of the spleen;• specific gravity of the spleen parenchyma - cellular elements of red and white pulps;• the specific weight of the connective tissue of the spleen;• the diameter of the central arteries and the thickness of the wall of the central arteries of the lymphatic follicles. Results. After the ligation of the splenic artery in the period of 1-3 days in the stroma and parenchyma of the spleen, reactive postoperative changes were observed. In the period of 7-10 days after surgical correction, the severity of the changes associated with an operational trauma, significantly decreases: significantly reduced the swelling of all structures of the spleen. The arteries of the spleen are spasmodic. This condition allows to maintain blood pressure in the blood vessels: there are blood elements in the сavity of the arteries. In the period of 30 days of experiment there is a normalization of the architectonic stroma and parenchyma of the organ. Disappearance of edema, capsules and trabecular fibers have a structure that is similar to the control group of animals. The layered structure of the lymphatic follicles of the spleen is restored and the follicles themselves are clearly separated from the red pulp. In the 90 days after the ligation of the splenic artery, changes in the spleen are characterized by the growth of its stroma. After 180 days of observation, a further increase in the proportion of connective tissue of the spleen and a decrease in the parenchyma of the spleen is observed. In this case, the parenchyma does not lose its properties, as indicated by the preservation of the architectonics of lymphatic follicles. Conclusions. As a result of the ligation of the splenic artery, the redistribution of intraorganic blood flow on the background of compensatory and adaptive reorganization, unfolding in the spleen in chronic portal hypertension, do not come to gross destructive changes in the morphological structures of the organ; in addition, in the remote postoperative period, they are restored.
Keywords: ligation of the spleen artery; portal hypertension; spleen